Bilingualism: Its influence on the reading comprehension of college students - Adybier M. Lobaton (Northern Negros State College of Science and Technology (NONESCOST), 2022)
Reading plays a great role in the lives of people. It provides them access to the world of ideas and an instrument for obtaining knowledge in various subject disciplines. It is a needed tool that one must possess so that s/he will not be deprived of a wonderful medium of learning. However, numerous factors impede one from acquiring reading skills. One of the most controversial issues on these factors is the language problem, which in the Philippines has evolved into an issue of national importance. Questions on the reading problem or language problem arise and it has continued to be the subject of national debate. This study was conducted utilizing the use of two languages (English and Filipino) in order to determine their significant influence on the reading comprehension of college students. A true-experimental method of research was used and it revealed: a) language of instruction does not affect significantly the achievement in reading comprehension of the subjects, b) results of the pre-test and post-test of both experimental and control groups consistently showed that the English and Filipino instructed-experimental and control group performed well in their reading achievement.